BENTUK NOMINA BAHASA MELAYU JAMBI DI DESA PENINJAU KECAMATAN BATHIN II PELAYANG KABUPATEN MUARA BUNGO PROVINSI JAMBI (KAJIAN MORFOLOGI) - ade rahima; Muhammad Juwanda (Universitas Batanghari, 2019)
This research is aimed at describing the form of noun in Jambi Malay language in di Desa Peninjau. This research is qualitative descriptive. Descriptively, this research identifies the form of noun in Jambi Malay language in Desa Peninjau. The data of this research is verbal oor utterances in the form of noun which are taken from 6 informants who are the native of Jambi Malay language in Desa Peninjau. The data is collected by using observation and interview. The data is analyzzed by using distribution analysis data in which the language itself. Based on the analysis of the data, it can be known that the form of noun in Jambi Malay language in Desa Peninjau comprises, monomorpheme noun and polimorpheme noun which can be developed more. The monomorpeme noun is one syllable , two syllables, and three syllables. While the polimorpheme noun is three syllables and four syllables.Keywords: Noun, Jambi Malay Language, Desa Peninjau